Membuka Pintu Menuju Sukses: Tips dan Trik Memanfaatkan Peluang di Dunia E-Bisnis - Muhammad Naufal Zahid Marpaung; Sofatun Nisa; Nabila Ismi; Nurbaiti Nurbaiti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This journal explores various important aspects in understanding, managing and exploiting opportunities in the world of e-business with the aim of achieving success. In an era where digital technology is changing the business landscape, e-business has become a source of innovation and limitless opportunities. In this context, this journal aims to provide readers with a comprehensive insight into how they can achieve success in the competitive world of e-business. In addition, this journal discusses effective marketing and promotional strategies in the online world, including the use of social media and digital advertising. In an effort to mitigate risk, we also discuss risk management in e-business and provide guidance on relevant business insurance.